KONSEP DASAR MANAJEMEN SUMBER DAYA MANUSIA PENDIDIKAN DALAM PENGUATAN KOMITMEN ORGANISASI GURU: SYSTEMATIC LITERATURE REVIEW - Nur Fahmuddin Hanif; Shera Nabila Luvianingtias; Rahayu Lestari; Junaidah Junaidah; Septuri Septuri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to examine the basic concepts of educational human resource management (HRM) in strengthening teachers' organizational commitment through a Systematic Literature Review (SLR) approach. The method used includes a literature search in reputable databases such as Google Scholar, Scopus, and ScienceDirect, with the inclusion criteria of national and international articles within the last five years that are relevant to the research topic. The analysis process is carried out through the stages of selection, extraction, and thematic synthesis of data to identify patterns of relationships between HRM practices and teachers' organizational commitment. The results of the study indicate that educational HRM has a strategic role in increasing organizational commitment through the functions of planning, competency development, performance evaluation, and providing teacher motivation and welfare. Teachers' multidimensional organizational commitment including affective, sustainability, and normative dimensions is significantly influenced by effective HRM practices, such as transformational leadership, a positive organizational culture, and a conducive work environment. In addition, organizational commitment acts as a mediating variable linking HRM with improved performance and positive work behaviors, such as Organizational Citizenship Behavior (OCB). Thus, the implementation of holistic, humanistic and sustainable HR is the key to strengthening the commitment of teacher organizations and improving the quality and competitiveness of educational institutions. ABSTRAK Penelitian ini bertujuan untuk mengkaji konsep dasar manajemen sumber daya manusia (MSDM) pendidikan dalam penguatan komitmen organisasi guru melalui pendekatan Systematic Literature Review (SLR). Metode yang digunakan meliputi penelusuran literatur pada database bereputasi seperti Google Scholar, Scopus, dan ScienceDirect, dengan kriteria inklusi artikel nasional dan internasional dalam lima tahun terakhir yang relevan dengan topik penelitian. Proses analisis dilakukan melalui tahap seleksi, ekstraksi, dan sintesis data secara tematik untuk mengidentifikasi pola hubungan antara praktik MSDM dan komitmen organisasi guru. Hasil kajian menunjukkan bahwa MSDM pendidikan memiliki peran strategis dalam meningkatkan komitmen organisasi melalui fungsi perencanaan, pengembangan kompetensi, evaluasi kinerja, serta pemberian motivasi dan kesejahteraan guru. Komitmen organisasi guru yang bersifat multidimensional—meliputi dimensi afektif, keberlanjutan, dan normatif—dipengaruhi secara signifikan oleh praktik MSDM yang efektif, seperti kepemimpinan transformasional, budaya organisasi yang positif, serta lingkungan kerja yang kondusif. Selain itu, komitmen organisasi berperan sebagai variabel mediasi yang menghubungkan MSDM dengan peningkatan kinerja dan perilaku kerja positif, seperti Organizational Citizenship Behavior (OCB). Dengan demikian, implementasi MSDM yang holistik, humanistik, dan berkelanjutan menjadi kunci dalam memperkuat komitmen organisasi guru serta meningkatkan kualitas dan daya saing lembaga Pendidikan